Sistematik Literatur Review: Pengaruh Model Pembelajaran terhadap Kemampuan Problem Solving pada Materi Kimia - Yoga Alfarizi; Dwi Afiqa; Miterianifa Miterianifa (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Problem-solving skills are a crucial 21st-century competency that students must master, but they are often a challenge in science education. This study aims to analyze the effectiveness of various innovative learning models on improving students' specific problem-solving skills in chemistry learning. Using the Systematic Literature Review (SLR) approach guided by the PRISMA protocol, this study examined nine accredited journal articles in the range of 2020 to 2025. The results of the data analysis showed that the Problem Solving (PS) and Project-Based Learning (PjBL) models emerged as the most dominant pedagogical interventions. Theoretically, the use of Polya indicators dominated the research framework by 50%, which proved to be significant in increasing students' N-Gain on abstract materials such as Thermochemistry and Redox Reactions. Furthermore, the effectiveness of this model reaches its optimum point when integrated with cutting-edge digital technologies, ranging from Virtual Laboratories and E-Modules to the use of Augmented Reality (AR), Google Sites, and the Educaplay platform. The research findings also confirm that the synergy of problem-based models with interactive media is able to increase high-level thinking skills (HOTS) and students' creativity with an Effect Size of 1.72. This study concludes that the application of constructivist learning integrated with cutting-edge digital technologies is essential for educators to bridge the understanding of theoretical concepts with the development of students' analytical and innovative skills in the digital age.